Various methods for Measuring Similarity and code clone detection - Kaur, Prabhjot; Agnihotri, Manoj (International Journal of Computer Sciences and Engineering, 2025)
Energy consumption is found to be critical task in today’s high performance computing. Consuming the energy in efficient way is still an open area of research. This paper has proved that the use of heuristics like Greedy method, Random method etc doesn’t provide consistent result every time when scheduling process is being run. Greedy can’t guarantee global optimal solution however Random method based upon certain global ability sometime may get best solution sometime may not. The use of variable neighbourhood search algorithm ignore in resistant task allocation for multicore processor. So in order to overcome these issues a variable neighbourhood search based approach is proposed to decrease the energy consumption rate.